The CuAAC: Principles, Homogeneous and Heterogeneous Catalysts, and Novel Developments and Applications - Neumann, Steve; Biewend, Michel; Rana, Sravendra; Binder, Wolfgang H. (Macromolecular rapid communications., 2020)
The copper‐catalyzed azide/alkyne cycloaddition reaction (CuAAC) has emerged as the most useful “click” chemistry. Polymer science has profited enormously from CuAAC by its simplicity, ease, scope, applicability and efficiency. Basic principles of the CuAAC are reviewed with a focus on homogeneous and heterogeneous catalysts, ligands, anchimeric assistance, and basic chemical principles. Recent developments of ligand design and acceleration are discussed. Copper‐I‐catalyzed “click” chemistry (CuAAC) has emerged as the most broadly useful click chemistry and has been widely applied in material science, bioorganic chemistry, and macromolecular chemistry. External additives and parameters (homogeneous/heterogeneous catalysts, ligands, anchimeric assistance, and basic chemical principles) are discussed, stressing polymer science's profit from CuAAC's complex chemistry, which allows for low Cu content in the final products.